The effect of progressive muscle relaxation on the psychological burden of caregivers of patients with diabetes mellitus - Uswatun Khasanah; Yossie Susanti Eka Putri; Mustikasari Mustikasari; Herni Susanti (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Type 2 Diabetes Mellitus (DM) is a chronic disease that not only affects patients but also places a significant psychological burden on their families as caregivers. This burden can take the form of stress, anxiety, depression, physical exhaustion, and decreased quality of life. Purpose: To determine the Progressive Muscle Relaxation (PMR) technique in reducing the psychological burden on caregivers of patients with DM type 2. Method: A descriptive qualitative approach, specifically focusing on exploratory study. The study took place April 2025, in Batutulis, Bogor. Using total sampling 2 participants were selected, contributor informant inquired Mr. W as caregiver and Mrs. U patients with diabetes mellitus type 2. Data collection in this study was done through triangulation, which combines several data sources, methods, and theories to increase the validity of the results. For data collection, it was conducted using indepth interviews were conducted with open-ended questions with questionnaire. The data were analysed using thematic analysis technique to identify important information and understand the core meaning of each data. Results: There was a decrease in psychological burden after the PMR intervention, as evidenced by a decrease in family questionnaire scores. Data collection was conducted through interviews, observation, and documentation. Conclusion: Progressive Muscle Relaxation has been shown to reduce the psychological burden on caregivers of patients with chronic illnesses, including diabetes. This intervention can be used as a supporting strategy for community nursing services to improve caregiver mental well-being.